Profitability Analysis in Improving Business Success - Rasyid, Ardiansyah; Setiawan , Levina; Mardjo , Johanna Aurielle (International Journal of Social Science and Community Service, 2024)
The rapid increase in the economy makes competition between companies to maintain its sustainability increasingly intense. How a company manages its working capital can affect the level of profitability of the company. PKM programmes are conducted to introduce the partners to profitability by managing the business partners' working capital. The training method uses zoom meetings and is assisted by two students. The material is presented in the form of PPT which includes: understanding profitability, managing receivables, payables, and inventory. The results of the activity show that training on profitability analysis has been carried out online and runs smoothly. The partner received the information and materials presented with enthusiasm, and asked questions during the activity process.